2000
DOI: 10.1902/annals.2000.5.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Implant Survival in Patients With Type 2 Diabetes: Placement to 36 Months

Abstract: Type 2 diabetic patients tend to have more failures than non-diabetic patients; however, the influence was marginally significant. These findings need to be confirmed by other scientific clinical studies with a larger Type 2 diabetic sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 16 publications
5
167
1
4
Order By: Relevance
“…The study of Morris et al (2000) was the only one associating some variables to diabetes and implant failure rates. They reported improved implant survival for patients who were treated with antibiotics in comparison with those treated without prophylactic antibiotics, but the survival improvement was greater in diabetic patients (97.1% vs. 86.6%) than in nondiabetic patients (95.1% vs. 90.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Morris et al (2000) was the only one associating some variables to diabetes and implant failure rates. They reported improved implant survival for patients who were treated with antibiotics in comparison with those treated without prophylactic antibiotics, but the survival improvement was greater in diabetic patients (97.1% vs. 86.6%) than in nondiabetic patients (95.1% vs. 90.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the microvascular disease leading to a diminished immune response and reduced bone turnover might be a contributing factor to implant failure (Olson et al, 2000), and that diabetes is one of several risk factors for implants that had survived until prosthetic loading (Morris et al, 2000).…”
Section: (B) Dental Implants In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…Hydroxyapatite plasma-spray-coated implants have been found to have a higher survival rate than titanium implants in type 2 diabetic patients, i.e., 97.9% vs. 84.7% after 36 months (Morris et al, 2000). This is noteworthy, since hydroxyapatite (HA) plasma-spray-coated implants are more susceptible to failure through microbial contamination, dissolution, and fracture of the HA from the titanium surface (Johnson, 1992).…”
Section: (C) Special Considerations For Implant Therapy In Patients Wmentioning
confidence: 99%
“…Most studies reviewed confirm these experimental results. In a 3-year retrospective study, a higher frequency of implant failure was shown in diabetic patients (7.8%) than in healthy patients (6.8%) [ 54 ].…”
Section: Dmentioning
confidence: 93%